Delirium, a Symptom of UTI in the Elderly: Fact or Fable? A Systematic Review(*) - Balogun, Seki A. (Canadian Geriatrics Society, 2013)
BACKGROUND: In geriatrics, delirium is widely viewed as a consequence of and, therefore, a reason to initiate workup for urinary tract infection (UTI). There is a possibility that this association is overestimated. To determine the evidence behind this clinical practice, we undertook a systematic review of the literature linking delirium with UTI. METHODS: A MEDLINE search was conducted from 1966 through 2012 using the MESH terms “urinary tract infection” and “delirium”, limited to humans, age 65 and older. The search identified 111 studies. Of these, five met our inclusion criteria of being primary studies that addressed the association of UTI and delirium. The studies were four cross-sectional observational studies and one case series. No randomized control trials were identified. All studies were published between 1988 and 2011. Four collected data retrospectively and one prospectively, with study sizes ranging from 14 to 1,285. The methodological strength of the studies was evaluated using six standards adapted from a previous systematic review. RESULTS: Only two of the five studies adequately matched or statistically adjusted for differences in comparison groups. None of the studies evaluated subjects with equal intensity for the presence of delirium and UTI, nor did they have objective criteria for either diagnosis. In subjects with delirium, UTI rates ranged from 25.9% to 32% compared to 13% in those without delirium. In subjects with UTI, delirium rates ranged from 30% to 35%, compared to 7.7% to 8% in those without UTI. CONCLUSIONS: Few studies have examined the association between UTI and delirium. Though the studies examined conclude that there is an association between UTI and delirium, all of them had significant methodological flaws that likely led to biased results. Therefore, it is difficult to ascertain the degree to which urinary tract infections cause delirium. More research is needed to better define the role of UTI in delirium etiology.